A 14-year series of leaf phenological data collected for European beech (Fagus sylvatica L.) and silver fir (Abies alba Mill.) from their geographic range margins in south-eastern France - Jean, Frederic; Davi, Hendrik; Oddou-Muratorio, Sylvie; Fady, Bruno; Scotti, Ivan; Scotti-Saintagne, Caroline; Ruffault, Julien; Journe, Valentin; Clastre, Philippe; Marloie, Olivier; Brunetto, William; Correard, Marianne; et al. (Annals of forest science., 2023)
Key message Phenology is of increasing interest to climate change science and adaptation ecology. Here, we provide bud development, leafing, and leaf senescence data, collected on 772 European beech and silver fir trees between 2006 and 2019 on Mont Ventoux, France. Dataset access is at https://doi.org/10.15454/TRFMZN . Associated metadata are available at https://metadata-afs.nancy.inra.fr/geonetwork/srv/fre/catalog.search#/metadata/a33c8375-9a90-4bc3-a0d7-19317160b68f .